[LB.03.01] LONG TERM CARDIAC STRUCTURE CORRELATES WITH ADVERSE PERINATAL COMPLICATIONS IN YOUNG ADULTS BORN PRETERM. (September 2017) - Mian, M.; Bigras, J.L.; Fernandes, R.; Bertagnolli, M.; Xie, L.F.; Paquette, K.; Wu, R.; Cloutier, A.; Orlando, V.; Luu, T.M.; Nuyt, A.M.
Abstract : Objective: Studies support a direct causal association between preterm birth and increased risk of cardiovascular diseases. Increased left and right ventricular mass and impaired systolic and diastolic function have been reported in young adults born preterm. Deleterious neonatal complications associated with preterm birth could significantly impact myocardial tissue. We assessed cardiac structure and function in young adults born extremely preterm (EPT) versus term and examined the impact of neonatal bronchopulmnonary dysplasia (BPD). Design and method: Eighty-five EPT (gestational age < 29 weeks) were recruited along with term-born controls matched for age, sex and socio-economic status. Birth data including neonatal parameters (gestational age, birth weight, BPD indicated by 36 weeks postnatal oxygen use) was collected. Ambulatory blood pressure (Spacelabs) and echocardiographic measurements (Phillips)were taken. Comparisons were performed using ANOVA or Student's t-test. Results: EPT presented with increased systolic (119 ± 9 vs 116 ± 8 mmHg, P < 0.05) and diastolic (68 ± 5 vs 66 ± 6 mmHg, P < 0.05) blood pressures. EPT exhibited reduced septal thickness (6.8 ± 0.8 vs 7.1 ± 1.1 mm, P < 0.05), left ventricular (LV) internal dimension (46 ± 4 vs 48 ± 5 mm, P < 0.05), LV end-diastolic (98 ± 20 vs 106 ± 24 ml/m 2, P < 0.05) and end-systolic (36 ± 9 vs 40 ± 11 ml, P < 0.01) volumes, right ventricular internal dimension (22 ± 3 vs 24 ± 4 mm, P < 0.05), and LV mass (104 ± 27 vs 115 ± 30 g, P < 0.05), but similar LV mass index and volume indexes. EPT exhibited increased LV myocardial performance index (0.41 ± 0.04 vs 0.39 ± 0.04, P < 0.01), reduced mitral lateral e' (17.6 ± 2.8 vs 19.1 ± 2.6 cm/s, P < 0.01), mitral s' (10.7 ± 2.3 vs 11.6 ± 2.3 cm/s, P < 0.01), tricuspid E' (15.8 ± 2.7 vs 16.8 ± 2.1 cm/s, P < 0.05), and tricuspid S' (13.1 ± 2.0 vs 14.0 ± 2.0 cm/s, P < 0.01) waves, and a trend in reduced mitral E wave (81 ± 14 vs 85 ± 15 cm/s, P = 0.09). EPT with neonatal BPD exhibited greater reduction in septal thickness (6.5 ± 0.8 mm, P < 0.05 vs terms and EPT without BPD), LV internal dimension (45 ± 4 mm, P < 0.05 vs terms), LV Mass (98 ± 22 g, P < 0.05 vs terms), and trend in reduced LV mass index (59 ± 10 g, P = 0.13 vs terms using T-test). Conclusions: EPT exhibit cardiac structural and functional alterations compared to term-born individuals. Neonatal BPD in EPT is a key contributor to long-term left ventricular remodeling.